KEPATUHAN WAJIB PAJAK: KEADILAN DAN PENGETAHUANPAJAK KPPMALANG SELATAN (Magister Manajemen Universitas Wisnuwardhana, 2019)
The purpose of this study was to determine the effect of fairness and taxknowledge on compliance of individual taxpayers in Malang. The analyticalmethod used in this study is multiple regression. Based on the results of theanalysis found evidence that simultaneously or partially justice and tax knowledgeaffect the compliance of Individual Taxpayers in Malang. In order to improvetaxpayer compliance, the KPP Pratama office in Malang provides taxationknowledge to the public through intensive, consistent and sustainable taxeducation. In addition, it is necessary to increase the quantity and quality of taxeducation counseling so that the public's tax knowledge increases and becomemore aware and compliant in carrying out their tax obligations. In addition,taxpayers to learn more and understand the regulations regarding taxation so thatthey can improve their compliance as taxpayers